The Effect Of Institutional Ownership, Managerial Ownership, And Company Size To Dividend Policy - Nugi Mohammad Nugraha; Samson Riki Johanes; R. Susanto Hendiarto (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
This research aims to determine the influence of variable Institutional Ownership, Managerial Ownership, and Firm Size to Dividend Policy in the sector company Consumer Goods listed on the Indonesia Stock Exchange 2013- 2018 period. The population of this research is the entire company contained in sector Consumer Goods listed on the Indonesia Stock Exchange 2013- 2018. The research samples consist of 12 companies used with purposive sampling methods and taken that meet with the criteria of a predetermined research sample. The data analysis method used is the analysis of the Data regression panel (Random Effect) with a status of the significance of 0.05. Based on the results of the research that has been done shows that simultaneously the Institutional Ownership variable, Managerial Ownership variable, and Firm Size variable affect the Dividend Policy. While partially shows that Institutional Ownership and Managerial Ownership do not have a partial effect on Dividend Policy. While Firm Size has a partial effect on Dividend Policy